Vitellogenesis in two spathebothriidean cestodes - Brunanská, Magdaléna; Poddubnaya, Larisa G; Dezfuli, Bahram S (Parasitology research, 2005)
Vitellogenesis in two spathebothriidean tapeworms, dixenous adult Cyathocephalus truncatus and monoxenous progenetic Diplocotyle olrikii, has been examined using transmission electron microscopy and cytochemical staining with periodic acid-thiosemicarbazide-silver proteinate for glycogen. Each vitelline follicle consists of vitellocytes at various stages of development and one irregularly shaped interstitial cell. Projections of the interstitial cell enclose the vitellocytes and extend as a cytoplasmic sheath on the follicular periphery. An outer thin fibrous layer (= extracellular lamina) covers the cytoplasmic sheath in C. truncatus, but lacks in D. olrikii. Maturing and mature vitellocytes contain vitelline material in the form of single small shell globules that gradually fuse and give rise to the large shell globule clusters. Morphology of shell globule clusters differs slightly in both species. In addition, single "lamellar" granules are present in the cytoplasm of vitellocytes of C. truncatus, but not in D. olrikii. Both electron lucent and electron dense lipid droplets are present in the vitellocytes of C. truncatus, whereas only electron dense lipids occur in D. olrikii. A single lipid droplet turns up occasionally in the nuclei of some of the vitellocytes of C. truncatus. The ultrastructural features of vitellogenesis in spathebothriideans resemble those reported previously in "lower" cestodes, especially in pseudophyllideans.
Keywords: Cestoda; Periodic Acid-Schiff Reaction; Vitellogenesis; vitelogeneze; glykogen; Animals; Glycogen; oocyty; Microscopy, Electron, Transmission; zvířata; transmisní elektronová mikroskopie; Schiffova reakce; Oocytes